Design and experimental study of a blended cement containing high-volume solid waste activated ultrafine powder. (11th October 2021) - Duan, Siyu; Wu, Hao; Liao, Hongqiang; Cheng, Fangqin
Highlights: A blended cement containing high-volume solid waste activated ultrafine powder (C-AUP) is designed. C-AUP has good physical and mechanical properties due to its excellent pore structure. The overall carbon footprint of the production of pure cement and C-AUP are compared and analyzed. Abstract: To improve the utilization efficiency of industrial solid waste and reduce the cost of cement production, a blended cement containing high-volume solid waste activated ultrafine powder (AUP) is designed and prepared. The experimental works are divided into two parts. In the first part, steel slag (SS), blast furnace slag (BFS), fly ash (FA), and desulfurized gypsum (DG) are separately ground and mixed properly to prepare a solid waste AUP, and the effect of the mixture properties on the activity index of the AUP is evaluated. The AUP with the highest activity index is selected in the second part to replace the cement at levels of 95%, 90%, 85%, 80%, and 75%, and the properties of the blended cement containing high-volume AUP (C-AUP) are analyzed. The C-AUP mortar is shown to exhibit higher compressive strength and lower heat of hydration than the control mortar. Compared with pure cement, the hydration degree of the C-AUP has a large gap. However, the C-AUP has fewer harmful pores and lower porosity, resulting in a high-strength mortar with a dense microstructure. In addition, carbon footprint analysis is conducted, the results of which show that the amount of CO2 released during C-AUP production is 270 kg/t less than that of pure cement.